EVALUATION OF THE ENTERPRISE'S ECONOMIC POTENTIAL - Khakimov Tulkin Halimovich (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective:  This article aims to analyze methods for assessing economic potential, evaluate key financial and production indicators, and propose practical approaches for agricultural enterprises to enhance their efficiency in Uzbekistan, where the strategic importance of rural development and food security is rising. Method: The study utilized systematic, comparative, statistical, and econometric methods to analyze production capacities, financial stability, profitability, and resource utilization. Result: Findings demonstrate that effective economic analysis must integrate quantitative assessments, such as liquidity and solvency ratios, with qualitative approaches including SWOT, PEST, and GAP analyses. Production capacity evaluation methods, such as monetary valuation, index, and resource-regression approaches, were identified as crucial for strategic planning. The research offers a holistic framework combining financial, production, and biological potential assessments, emphasizing the role of innovative and diversification strategies in strengthening enterprise resilience. Novelty: Despite existing studies, comprehensive methodological frameworks for evaluating economic potential that consider sector-specific factors remain underdeveloped in Uzbekistan, and this study contributes a synthesized, integrative framework tailored specifically to the agricultural sector to support evidence-based decision-making.